2018
DOI: 10.1289/ehp2619
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of Perfluoroalkyl Substances and Risk of Type 2 Diabetes: A Prospective Investigation among U.S. Women

Abstract: Background:Emerging evidence suggests that perfluoroalkyl substances (PFASs) are endocrine disruptors and may contribute to the etiology of type 2 diabetes (T2D), but this hypothesis needs to be clarified in prospective human studies.Objectives:Our objective was to examine the associations between PFAS exposures and subsequent incidence of T2D in the Nurses’ Health Study II (NHSII). In addition, we aimed to evaluate potential demographic and lifestyle determinants of plasma PFAS concentrations.Methods:A prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(83 citation statements)
references
References 83 publications
1
82
0
Order By: Relevance
“…Moreover, studies have shown that microwave popcorn packaging contains perfluoroalkyl substances, a group of anthropogenic chemicals with endocrine disrupting properties, which can contaminate popcorn 5657. Several studies showed that these compounds were associated with poor glucose metabolism,5859 weight gain,60 and an increased risk of type 2 diabetes 61. Previous research showed that higher popcorn intake was often correlated with a snacking pattern that is associated with weight gain62 and a risk of diabetes 63.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have shown that microwave popcorn packaging contains perfluoroalkyl substances, a group of anthropogenic chemicals with endocrine disrupting properties, which can contaminate popcorn 5657. Several studies showed that these compounds were associated with poor glucose metabolism,5859 weight gain,60 and an increased risk of type 2 diabetes 61. Previous research showed that higher popcorn intake was often correlated with a snacking pattern that is associated with weight gain62 and a risk of diabetes 63.…”
Section: Discussionmentioning
confidence: 99%
“… 48 , 49 This hypothesis was postulated by the European Youth Heart Study, in which investigators observed lower waist circumference with higher PFOA concentrations cross-sectionally. 23 In addition, diet is a major source of PFASs and fast food might be an important route of exposure, 50 , 51 as might fish consumption, 52 , 53 potentially confounding associations bidirectionally. However, we measured plasma PFAS concentrations at baseline, measured change in body outcomes prospectively, and participants were randomized to study arms, minimizing but not eliminating the chance for dietary habits to confound the results.…”
Section: Discussionmentioning
confidence: 99%
“…PFASs, on the other hand, are a group of man-made chemicals that have been widely used since the 1950s in both household and industrial products. PFASs also have long biological half-lives, and are readily detected in humans [3][4][5][6][7]. Structurally, several PFAS compounds resemble endogenous fatty acids, with fluorine substitution in place of hydrogen.…”
Section: Introductionmentioning
confidence: 99%